Clinical features of febrile neutropenia and bloodstream infection in autologous hematopoietic cell transplantation: Comparison to those in intensive chemotherapy for acute myeloid leukemia. Issue 4 (April 2023) - Yoshino, Nozomu; Kimura, Shun-ichi; Matsuoka, Akari; Meno, Tomohiro; Ishikawa, Takuto; Nakamura, Yuhei; Kawamura, Masakatsu; Takeshita, Junko; Kawamura, Shunto; Misaki, Yukiko; Yoshimura, Kazuki; Gomyo, Ayumi; et al.
Abstract: Background: In autologous hematopoietic cell transplantation (HCT), myelosuppression and mucosal damage are more severe than those in conventional chemotherapy because of high-dose chemotherapy, but the duration of neutropenia is shorter due to stem cell rescue. Methods: We retrospectively evaluated febrile neutropenia (FN) and bloodstream infection (BSI) in 208 patients who underwent their first autologous HCT at our institution between 2007 and 2019. They were compared to those in patients who underwent intensive chemotherapy for acute myeloid leukemia (AML) (130 induction/salvage and 191 consolidation). Results: The median neutropenic period in autologous HCT, AML induction/salvage and consolidation was 9, 26.5, and 19 days, respectively. The incidence of FN was 93.8%, 92.3%, and 81.7%, and that of BSI in initial FN was 7.2%, 7.5% and 26.3%, respectively. The incidence of oral mucositis (≥ grade 2) was 63.1%, 9.2% and 12.2%, and that of diarrhea (≥ grade 2) was 53.3%, 9.2% and 6.4%, respectively. Although there were significant differences in the incidence of shaking chills, the degree of fever and the value of CRP between patients with and without BSI in initial FN of AML chemotherapy, no significant risk factors or predictive factors for BSI were identified in autologous HCT. Conclusions: The profile of infectious complications in autologous HCT was characterized by a high incidence of FN maybe due to mucosal damage. On the other hand, the incidence of BSI was lower compared to that in AML consolidation chemotherapy.